An examination of restaurant firm financing and the cost of borrowing. Issue 2 (15th March 2017) - Dalbor, Michael C.; Lee, Seoki
ABSTRACT: The use of debt is prevalent in the restaurant industry. While there have been numerous studies on restaurant capital structure, this study examines the relationship between firm performance and effective interest rate on debt used by restaurant firms. This study uses a sample of 56 publicly traded U.S. restaurant firms for the years 2012–2014. We examine the relationship between effective interest rates and firm performance as measured by approximate Tobin's Q, return on assets, and return on equity. We find a significant and positive relationship between effective interest rates and return on equity.